Molecular genetic profiling of a rare case of primary pulmonary adenoid cystic carcinoma: Insights from whole exome sequencing and literature review - Jianhao Xu; Fang Cao; Liqian Yao; Jingfeng Gu; Lanfen Pan; Jiarui Min; Zijie Xu; Jihao Su; Zhiyong Deng; Song Xu (Respiratory Medicine Case Reports)
Background: Primary pulmonary adenoid cystic carcinoma (PPACC) is a rare neoplasm characterized by slow growth and low malignancy. Aim: The study seeks to enhance understanding of PPACC through comprehensive analysis of a reported case, incorporating pathological diagnosis, immunohistochemistry, special staining, and molecular alterations identified via whole exome sequencing. Methods: A retrospective analysis was conducted on a PPACC case treated at the institution, encompassing pathological examination, immunohistochemical profiling, special staining techniques, and molecular alterations revealed by whole exome sequencing. Results: A 56-year-old male presented with a left lower lobe mass identified on chest CT during a routine health check. Clinical evaluation revealed dyspnea, and imaging showed a 25 × 18 mm nodule in the left lower lobe. Video-assisted thoracoscopic surgery was performed for left lower lobectomy, with intraoperative frozen pathology indicating a salivary gland-type tumor (2.5 × 2 × 1.7 cm). ENT examination and cervical MRI ruled out a primary salivary gland tumor. Routine paraffin-embedded pathology confirmed pulmonary adenoid cystic carcinoma without pleural invasion. Whole exome sequencing revealed mutations in MYB family genes and the ALK gene. Conclusion: This study highlights the pathological and molecular characteristics of PPACC, including a cribriform pattern and specific genetic mutations. These findings underscore the necessity of enhancing clinical vigilance to avoid misdiagnosis and missed diagnosis of this disease.